Challenges of sustaining design identity in Chinese Taoist temples built in the 19th century in Klang Valley, Malaysia - Yeong, Yin Mei; Abd Rahman, Khairul Aidil Azlin; Ismail, Nor Atiah; Utaberta, Nangkula (Universiti Putra Malaysia Press, 2020)
Traditionally, Chinese philosophy has revealed the principle of building materials as Earth and Wood (土木). The principle applies to various buildings worldwide including the Chinese Taoist temples. The objective of this paper was to examine the interior design and materials applied within the Chinese Taoist temples built during the 19th century in Klang Valley, Malaysia, based on design typology. A qualitative research methodology was employed which involved semi-structured interviews and direct observation of ten selected Chinese Taoist temples (N=10) within Klang Valley. Interviews were recorded and sketches and photographs were compiled. The data were analysed using content analysis. The results showed that over the past century, the buildings had lost their design identity due to a lack of proper maintenance and design guideline. It was also revealed that the Chinese community, despite having many years of experience working in temples, lacks understanding in handling the preservation of the buildings. This has eventually resulted in the dramatic dismissal of the original design character. A benchmark for restoration and conservation of the buildings has to be established for the Chinese community via certain platform to ensure that the “sustainability” of ancient designs within the Chinese Taoist temples is able to propagate to the next generation.